Teaching Phrasemes by Applying Ludic Elements - Świątek, Zuzanna (Ludicity in (Glotto)Didactic, 2020)
It should be noted that phrasemes are usually difficult to remember, which is why it is vital for the teacher to choose the appropriate methods. Regardless of the age group, the use of a ludic strategy should be a significant element of foreign language lessons when teaching idiomatic phrases in order to improve the learning process. The aim of this paper is to examine the knowledge that students of Roman philology have in the field of phraseology of the French language and their knowledge of the accelerated learning techniques, very often used in the ludic strategy. The introduction of memory techniques during classes contributes to a lasting memorization of a given idiomatic expression, as well as the development of student’s creativity. Play-based learning also encourages students to actively participate in lessons, which translates into didactic effects. The research investigated the knowledge of certain idiomatic phrases among the students of Roman studies as well as their individual learning techniques. The analysis of the survey shows that students do not have enough knowledge in the field of foreign language phraseology. What is more, most of them have never encountered any exercises based on memorization techniques. Apart from the didactic, the linguistic aspect is also presented to help understand the differences and similarities between the phraseological compounds.